Effects of Dapagliflozin in Stage 4 Chronic Kidney Disease - Chertow, Glenn M.; Vart, Priya; Jongs, Niels; Toto, Robert D.; Gorriz, Jose Luis; Hou, Fan Fan; McMurray, John J.V.; Correa-Rotter, Ricardo; Rossing, Peter; Sjöström, C. David; Stefánsson, Bergur V.; Langkilde, Anna Maria; et al. (Journal of the American Society of Nephrology, 2021)
Significance Statement Relatively little is known about the relative safety and efficacy of sodium-glucose cotransporter 2 (SGLT2) inhibitors in patients with advanced (stage 4) CKD. The Dapagliflozin and Prevention of Adverse Outcomes in Chronic Kidney Disease (DAPA-CKD) trial enrolled patients with CKD with or without type 2 diabetes (mean eGFR 43 ± 12 ml/min per 1.73m2), finding that patients receiving the drug had lower risks of major kidney and cardiovascular events and an attenuation of progressive eGFR loss compared with patients receiving placebo. In this analysis within a subgroup of patients with stage 4 CKD and albuminuria, the authors found that the benefits of the SGLT2 inhibitor dapagliflozin in patients with baseline eGFR<30 ml/min per 1.73m2 were consistent with those observed in the DAPA-CKD trial overall, with no evidence of increased risks. Background In the Dapagliflozin and Prevention of Adverse Outcomes in Chronic Kidney Disease (DAPA-CKD) randomized, placebo-controlled trial, the sodium-glucose cotransporter 2 inhibitor dapagliflozin significantly reduced risk of kidney failure and prolonged survival in patients with CKD with or without type 2 diabetes. Methods Adults with eGFR of 25-75 ml/min per 1.73 m2 and urinary albumin-to-creatinine ratio of 200-5000 mg/g had been randomized to receive dapagliflozin 10 mg/d or placebo. Here, we conducted a prespecified analysis of dapagliflozin's effects in patients with stage 4 CKD (eGFR,30 ml/min per 1.73 m2) at baseline. The primary end point was a composite of time to ≥50% sustained decline in eGFR, ESKD, or kidney or cardiovascular death. Secondary end points were a kidney composite (same as the primary end point but without cardiovascular death), a composite of cardiovascular death or heart failure hospitalization, and all-cause death. Results A total of 293 participants with stage 4 CKD received dapagliflozin and 331 received placebo. Patients with stage 4 CKD randomized to dapagliflozin experienced a 27% (95% confidence interval [95% CI]: −2 to 47%) reduction in the primary composite endpoint, and 29% (−2 to 51%), 17% (−53 to 55%), and 32% (−21 to 61%) reductions in the kidney, cardiovascular and mortality endpoints, respectively, relative to placebo. Interaction P-values were 0.22, 0.13, 0.63, and 0.95, respectively, comparing CKD stages 4 versus 2/3. The eGFR slope declined by 2.15 and 3.38 ml/min per 1.73 m2 per year in the dapagliflozin and placebo groups, respectively (P=0.005). Patients treated with dapagliflozin or placebo had similar rates of serious adverse events and adverse events of interest. Conclusions Among patients with stage 4 CKD and albuminuria, the effects of dapagliflozin were consistent with those observed in the DAPA-CKD trial overall, with no evidence of increased risks.